STRATEGIES IN TERMINOLOGY KNOWLEDGE - Mamajanova, Guncha (Журнал иностранных языков и лингвистики, 2023)
The purpose of this article is to help students become more effective in studying technical English. This means developing their ability to understand, interpret, process and use the technical vocabulary contained not only in the reading material, but also ways of translation special terms.